Life Course Epidemiology on the Determinants of Stunting in Children Under Five in East Lombok, West Nusa Tenggara - Sajalia, Husniyati; Dewi, Yulia Lanti Retno; Murti, Bhisma (Journal of Maternal and Child Health, 2018)
Background: Stunting remains a challenging global health issue. It is estimated by Global Nutrition Report that 155 million children were stunted in 2017. Stunting is associated with an underdeveloped brain, with long-lasting harmful consequences, including diminished mental ability and learning capacity, poor school performance in childhood, reduced earnings and increased risks of nutrition-related chronic diseases, such as diabetes, hypertension, and obesity in future. This study aimed to examine the determinants of stunting in children under five in East Lombok, West Nusa Tenggara.Subjects and Method: This was an analytic observational study with a case control design. The study was carried out in 31 posyandus (integrated family health posts) in East Lombok, West Nusa Tenggara, from April to May 2018.A sample of 186 children was selected by fixed disease sampling. The dependent variable was stunting. The independent variables were low birthweight (LBW), birth length, exclusive breastfeeding, history of infection disease, maternal age at pregnancy, maternal middle upper arm circumference (MUAC), and family income. The data were collected by questionnaire and analyzed by a multilevel logistic regression run in Stata 13.Results: The risk of stunting increased with LBW (b= 3.51; 95% CI= -0.28 to 7.31; p= 0.069), maternal age at pregnancy <20 or ?35 years (b= 2.73; 95% CI= 0.38 to 5.42; p=0.047), andhistory of infectious disease (b= 3.70; 95% CI= 0.84 to 6.56; p=0.011). The risk of stunting reduced with high family income (b= -2.15; 95% CI= -4.37 to 0.61; p=0.057), birth length (b= -4.17; 95% CI= -7.42 to -0.91; p=0.012), exclusive breastfeeding (b= -3.24; 95% CI= -5.63to -0.85; p=0.008), and maternal MUAC ?23.5cm (b= -4.53; 95% CI= -8.09to -0.97; p=0.013). Posyandu had a contextual effect on the incidence of child stunting with ICC= 15.00%.Conclusion: The risk of stunting increases with LBW, maternal age at pregnancy <20 or ?35 years, and history of infectious disease. The risk of stunting reduces with high family income, birth length, exclusive breastfeeding, and maternal MUAC. Posyandu has a contextual effect on the incidence of child stunting.Keywords: Stunting, low birthweight, birth length, exclusive breastfeedingCorrespondence:Husniyati Sajalia. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami No. 36 A, Surakarta 57126, Central Java. Email: sajalia@gmail.com. Mobile: +6281997987081Journal of Maternal and Child Health (2018), 3(4): 242-251https://doi.org/10.26911/thejmch.2018.03.04.01